Recent Advances in the Development of Thin Films (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Thin-film coating technology has revolutionized various industries by offering functional solutions that enhance efficiency, flexibility, and performance in electronic devices, optics, solar cells, hard coatings, sensors, and even food preservation. This cutting-edge technology has significantly contributed to advancements in nanotechnology, materials science, and renewable energy. This Special Issue, comprising thirteen high-quality contributions, showcases a portion of the ongoing dynamism and diversity within thin-film research. It covers several key areas related to recent advancements in thin-film development, including deposition and characterization techniques, mechanical and electrical properties, sensing and solar cell technologies, food preservation and advanced approaches for assessing the mechanical behavior of thin films. The presented research reflects not only the current state-of-the-art but also offers new perspectives for future advancements across various industries and technologies.